2018
DOI: 10.5194/hess-22-3575-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a multiresolution snow reanalysis framework: a multidecadal reanalysis case over the upper Yampa River basin, Colorado

Abstract: Abstract. A multiresolution (MR) approach was successfully implemented in the context of a data assimilation (DA) framework to efficiently estimate snow water equivalent (SWE) over a large head water catchment in the Colorado River basin (CRB), while decreasing computational constraints by 60 %. A total of 31 years of fractional snow cover area (fSCA) images derived from Landsat TM, ETM+, and OLI sensor measurements were assimilated to generate two SWE reanalysis datasets, a baseline case at a uniform 90 m spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The 30 m fSCA data is then aggregated to the desired reanalysis model resolution. Previous regional applications have used 90 m (Margulis et al, 2016a), 180 m (Cortes and Margulis, 2017) and a multi-resolution approach (Baldo and Margulis, 2018). For the ultimate application to the large-scale HMA domain, and to make the Landsat fSCA of consistent scale with the MODIS-based fSCA, we herein used an aggregated resolution of ∼480 m (16 arcsecond grid).…”
Section: Landsat-based Fsca Datamentioning
confidence: 99%
“…The 30 m fSCA data is then aggregated to the desired reanalysis model resolution. Previous regional applications have used 90 m (Margulis et al, 2016a), 180 m (Cortes and Margulis, 2017) and a multi-resolution approach (Baldo and Margulis, 2018). For the ultimate application to the large-scale HMA domain, and to make the Landsat fSCA of consistent scale with the MODIS-based fSCA, we herein used an aggregated resolution of ∼480 m (16 arcsecond grid).…”
Section: Landsat-based Fsca Datamentioning
confidence: 99%
“…applied a similar setup to conduct a snow reanalysis for the extratropical Andes Aalstad et al (2018). compared the performance of the PBS with ensemble Kalman-based smoothers when assimilating FSCA data from Sentinel-2 and MODIS for sites in the high-Arctic and found that the PBS markedly outperformed non-iteratve ensemble Kalman-based smoothers in line withMargulis et al (2015) Baldo and Margulis (2018). developed a multi-resolution snow reanalysis framework using the PBS and demonstrated, through tests in a basin in Colorado, that this could match the performance of the original single-resolution approach at a fraction of the computational cost.…”
mentioning
confidence: 99%
“…As such, to our knowledge, 4D-Var has not been applied in snow cover applications. Other smoother methods, namely the Ensemble Kalman Smoother (EnKS) and the Particle Batch Smoother (PBS), which are essentially smoother extensions of the filtering approaches outlines above, have been applied in snow hydrology recently with a variety of data assimilated including passive/active microwave and SCA/SCF (e.g., Durand et al, 2009;Bateni et al, 2013Bateni et al, , 2015Girotto et al, 2014;Margulis et al, 2015Margulis et al, , 2016Margulis et al, , 2019bCortés and Margulis, 2017;Li et al, 2017;Aalstad et al, 2018;Baldo and Margulis, 2018). In the EnKS, a Kalman update can be performed on all states over a given window, while in the PBS, particle weights are updated by conditioning on all measurements over the assimilation window.…”
Section: Retrospective Data Assimilation Methodsmentioning
confidence: 99%